High-conductivity free-cutting copper alloy material and preparation method thereof
By optimizing the composition and process of copper alloys, a copper alloy material with high conductivity and easy cutting was prepared, solving the problem of balancing conductivity and cutting performance, and realizing a simple preparation method and low-cost industrial production.
Patent Information
- Application Number
- CN202511491392.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-18
- Publication Date
- 2026-01-23
AI Technical Summary
Existing copper alloy materials struggle to achieve a balance between electrical conductivity and machinability, and their complex and costly preparation methods limit their large-scale production and application.
By optimizing the composition of copper alloys and employing smelting, casting, hot extrusion, and cold working processes, controlling the content of alloying elements such as Te, Fe, and B, and using specific equipment and processes, such as medium-frequency induction melting furnaces and hydraulic drawing machines, highly conductive and easily machinable copper alloy materials can be prepared.
The prepared copper alloy material has high electrical conductivity and good machinability, making it suitable for large-scale industrial production, reducing production costs, and improving processing efficiency and surface quality.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of alloy smelting, and particularly relates to a high-conductivity and easy-to-cut copper alloy material and a preparation method thereof. BACKGROUND
[0002] With the rapid development of modern industry, the performance requirements for copper alloy materials are becoming higher and higher. In the fields of electronics, electrical appliances, and mechanical manufacturing, a copper alloy material with both high conductivity and good cutting performance is needed. High conductivity can ensure current transmission efficiency and reduce energy loss, and good cutting performance can improve processing efficiency and reduce processing cost, meeting the processing needs of precision parts.
[0003] However, the commonly used copper alloy materials at present often cannot achieve an ideal balance between conductivity and cutting performance. For example, some copper alloys have high conductivity but poor cutting performance, and problems such as serious tool wear and poor surface quality occur during processing; while other copper alloys have good easy-to-cut performance but their conductivity cannot meet the requirements of some harsh application scenarios. In addition, the existing preparation methods of copper alloys have the disadvantages of complex process, high production cost, and long preparation period, which limit their large-scale production and application.
[0004] Therefore, it is urgent to develop a new copper alloy material with both high conductivity and easy-to-cut performance and a preparation method thereof to meet the requirements of industrial development for material performance and production cost, which has important practical significance and market value, and the problem needs to be solved. SUMMARY
[0005] The application is to solve the above technical problems, and provides a high-conductivity and easy-to-cut copper alloy material and a preparation method thereof. The technical purpose of the application is to optimize the alloy composition and the preparation process, so that the prepared copper alloy material has both high conductivity and good cutting performance, and the preparation method is simple in process and low in cost, which is suitable for large-scale industrial production.
[0006] In order to achieve the above technical purpose, the technical scheme adopted by the application is as follows:
[0007] The application first provides a preparation method of a high-conductivity and easy-to-cut copper alloy material. The element composition of the high-conductivity and easy-to-cut copper alloy material is as follows in terms of weight percentage: Te=0.6-0.7%, Fe=0.0020-0.0060%, B=0.0020-0.0060%, and Cu is the balance. The preparation method comprises the following steps:
[0008] (1) Melting: the cathode copper is added to a melting furnace, flake graphite is used as a covering agent, and the temperature is raised to 1100-1200°C to completely melt the cathode copper; the boron-copper alloy, tellurium, and iron alloy elements are sequentially added to the copper liquid, the temperature range is 1200°C±10°C, and the alloy elements are continuously stirred during the adding process to promote the uniform dispersion of the alloy elements in the copper liquid, the stirring speed is controlled at 200-300 r / min, and the stirring time is 10-15 min after each addition of the alloy elements; after the addition is completed, the furnace temperature is raised to 1200-1250°C, and the temperature is maintained for 15-20 min to further homogenize the alloy components;
[0009] (2) Casting: the alloyed copper liquid is cast into a high-purity graphite mold preheated to 200-300°C, and the casting temperature is 1170-1190°C; the casting speed is controlled at 5-10 kg / min, and the mold is kept stable during the casting process to avoid turbulence of the copper liquid, thereby obtaining a copper alloy ingot;
[0010] (3) Extrusion: the copper alloy ingot obtained in step (2) is placed in an induction heating furnace, heated to 800°C±10°C, and maintained for 30 min, and then subjected to water-sealed extrusion deformation processing;
[0011] (4) Pickling and hydraulic drawing: the extruded material obtained in step (3) is pickled to remove surface oxides, and then subjected to hydraulic drawing, with a total deformation of 50% and a single pass deformation of 15%-25%;
[0012] (5) The drawn rod is straightened, polished, and cut to size.
[0013] Further, the copper content Cu% in the cathode copper in step (1) is ≥99.95%, and the melting furnace is a medium-frequency induction melting furnace.
[0014] Further, the carbon content C% of the flake graphite in step (1) is ≥99.95%.
[0015] Further, the boron content B% of the boron-copper alloy is 5%±1%.
[0016] Further, the tellurium is high-purity tellurium, and the tellurium content Te% is ≥99.95%.
[0017] Further, the iron is high-purity iron powder, and the iron content Fe% is ≥99.95%.
[0018] Further, the water-sealed extrusion deformation processing in step (3) is performed on an 800 horizontal extruder, and the equipment specification is 8.0 MN.
[0019] Further, the extrusion in step (3) adopts a reverse extrusion method, and the extrusion temperature is 800°C±10°C.
[0020] Further, the die material used in the extrusion in step (3) is metal inlaid ceramic, and the extrusion ratio is 20-150.
[0021] Further, the pickling in step (4) is to place the extruded blank in a sulfuric acid tank with a concentration of 15-20%.
[0022] Further, the drawing die in step (4) is an alloy drawing die or a diamond-coated drawing die, and the drawing die specification is:
[0023] Further, the hydraulic drawing in step (4) is carried out in a hydraulic drawing machine, and the specification is 0.6 MN.
[0024] The second object of the present application is to provide a copper alloy material prepared by the above method, which simultaneously has high electrical conductivity and easy cutting performance.
[0025] The beneficial effects of the present application are as follows:
[0026] (1) High electrical conductivity: By optimizing the alloy composition, especially strictly controlling the content of elements such as tellurium, iron, boron, etc., the prepared copper alloy material has high electrical conductivity, and the electrical conductivity can reach more than 90% IACS, meeting the demand for high-conductivity materials in the fields of electronics and electrical appliances.
[0027] (2) Good cutting performance: The specific element combination and microstructure in the alloy make the material easy to break during cutting, the tool wears less, the cutting force is low, and the cutting performance is good, which can reach more than 80% of the cutting performance of HPb63-3 material under the same conditions, improving the processing efficiency and the quality of the processed surface.
[0028] (3) Simple preparation process: The preparation method of the present application adopts common melting, casting, hot extrusion forming, and cold working process, which is simple and easy to operate and control, does not require complex equipment and special process conditions, is suitable for large-scale industrial production, and can effectively reduce the production cost.
[0029] (4) Stable material performance: By strictly controlling the process parameters during preparation, the uniformity of the alloy composition and the stability of the microstructure are ensured, so that the prepared copper alloy material has stable performance, reliable quality, and good consistency, which is beneficial to the quality control and application promotion of the product.
[0030] (5) The tensile strength of the copper alloy rod obtained by the method of the present application is ≥350 MPa. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present application more clear, the present application is described in detail below with examples. It is necessary to point out that the following examples are only used to explain and describe the present application, and do not limit the present application. Some non-essential improvements and adjustments made by the person skilled in the art according to the above description still belong to the protection scope of the present application.
[0032] Example 1
[0033] A high-conductivity free-cutting copper alloy material, whose elemental composition is as follows in terms of percentage by weight:
[0034] Raw materials: 99.33 kg of electrolytic copper with a purity of 99.95%, 0.62 kg of tellurium with a purity of 99.95%, 0.0025 kg of iron with a purity of 99.95%, and 0.05 kg of boron-copper intermediate alloy.
[0035] The preparation method of the above copper alloy material comprises the following steps:
[0036] (1) Melting: cathode copper is added into a medium-frequency induction melting furnace, and heated to 1150℃ to melt it; boron-copper intermediate alloy, tellurium and iron are sequentially added, and the stirring speed is 250 r / min, and each addition is stirred for 12 min; then the furnace temperature is increased to 1200℃, and the temperature is kept for 20 min.
[0037] (2) Casting: the alloyed copper liquid is cast into a high-purity graphite mold preheated to 250℃, the casting speed is 8 kg / min, and the casting temperature is 1185℃, so as to obtain a copper alloy ingot.
[0038] (3) Hot extrusion: the obtained copper alloy ingot is placed into an induction furnace, heated to 800℃, and kept for 30 min to make the crystal grains uniform and refined, and then extrusion deformation processing is performed; the extrusion deformation processing is performed on an 800-type horizontal extruder, and the equipment specification is 8.0 MN. The extrusion adopts a reverse extrusion mode, the extrusion die adopts an inlaid ceramic, and the size of the extrusion die is: outer circle inner hole
[0039] (4) Pickling and hydraulic drawing: the obtained blank is pickled, the blank after extrusion is placed in a 15% sulfuric acid tank for pickling to remove the surface oxides, and then hydraulic drawing is performed; the hydraulic drawing is performed on a hydraulic drawing machine, and the equipment specification is 0.6 MN. The specification of the alloy drawing die is: (drawn process: ), and uniform drawing is performed.
[0040] (5) The rod after the above drawing deformation is straightened, polished and sized, and the high-conductivity free-cutting copper alloy material is obtained.
[0041] The copper alloy material obtained is subjected to performance inspection, ten samples are taken from each batch, and the average value is taken. The metal material tensile test refers to the standard GB / T228, the metal material bending test is in accordance with the standard GB / T232, and the conductivity detection method is in accordance with the provisions of the standard GB / T351 for metal material resistivity measurement method. The mechanical properties of the copper alloy material obtained are: tensile strength Rm=370 MPa, machinability=83%, elongation=15%, and electrical conductivity=92% IACS.
[0042] Example 2
[0043] A high-conductivity and easy-to-machine copper alloy material, the elemental composition of which is as follows in terms of percentage by weight:
[0044] Raw materials: 99.28 kg of electrolytic copper with a purity of 99.95%, 0.64 kg of tellurium with a purity of 99.95%, 0.004 kg of iron with a purity of 99.95%, and 0.08 kg of boron-copper intermediate alloy.
[0045] The preparation method of the above-mentioned copper alloy material comprises the following steps:
[0046] (1) Melting: cathode copper is added to a medium-frequency induction melting furnace, and heated to 1160°C to melt it; boron-copper intermediate alloy, tellurium, and iron are sequentially added, with a stirring speed of 200 r / min, and stirring for 10 min after each addition; then the furnace temperature is raised to 1220°C, and the temperature is maintained for 18 min.
[0047] (2) Casting: the alloyed copper liquid is cast into a high-purity graphite mold preheated to 200°C, with a casting speed of 5 kg / min and a casting temperature of 1190°C, to obtain a copper alloy ingot.
[0048] (3) Hot extrusion: the obtained copper alloy ingot is placed in an induction furnace and heated to 800°C for 30 min to uniformly refine the grains, and then subjected to extrusion deformation processing; the extrusion deformation processing is carried out on an 800-type horizontal extruder with a specification of 8.0 MN. The extrusion is carried out in a reverse extrusion mode, the extrusion die is embedded with ceramic, and the size of the extrusion die is: Outside circle Inside hole
[0049] (4) Pickling and hydraulic drawing: the obtained blank is pickled by placing the blank obtained after extrusion in a 15% sulfuric acid tank to remove surface oxides, and then subjected to hydraulic drawing; the hydraulic drawing is carried out on a hydraulic drawing machine with a specification of 0.6 MN. The specification of the alloy drawing die is: (Drawing process: ), uniform drawing.
[0050] (5) The rod after the above drawing deformation is straightened, polished and sized, and thus obtained.
[0051] The obtained copper alloy material is subjected to performance inspection, ten samples are taken from each batch, and the average value is taken. The metal material tensile test refers to the standard GB / T228, the metal material bending test is in accordance with the standard GB / T232, and the conductivity detection method is in accordance with the provisions of the standard GB / T351 for metal material resistance coefficient measurement. The mechanical properties of the obtained copper alloy material are: tensile strength Rm = 365 MPa, machinability = 83%, elongation = 16%, and conductivity = 91% IACS.
[0052] Example 3
[0053] A high-conductivity and easy-to-machine copper alloy material, the elemental composition of which is as follows in terms of percentage by weight:
[0054] Raw materials: 99.22 kg of electrolytic copper with a purity of 99.95%, 0.66 kg of tellurium with a purity of 99.95%, 0.006 kg of iron with a purity of 99.95%, and 0.12 kg of boron-copper intermediate alloy.
[0055] The preparation method of the above-mentioned copper alloy material comprises the following steps:
[0056] (1) Melting: The cathode copper is added to a medium-frequency induction melting furnace, and heated to 1180°C to melt it; the boron-copper intermediate alloy, tellurium and iron are sequentially added, and the stirring speed is 300 r / min, and each addition is stirred for 15 min; then the furnace temperature is raised to 1250°C, and the temperature is maintained for 15 min.
[0057] (2) Casting: The alloyed copper liquid is cast into a high-purity graphite mold preheated to 300°C, the casting speed is 10 kg / min, and the casting temperature is 1175°C, and a copper alloy ingot is obtained.
[0058] (3) Hot extrusion: The obtained copper alloy ingot is placed in an induction furnace, heated to 800°C, and kept for 30 min to make the grains uniform and fine, and then subjected to extrusion deformation processing; the extrusion deformation processing is carried out on an 800 horizontal extruder with a specification of 8.0 MN. The extrusion adopts a reverse extrusion mode, the extrusion die adopts an inlaid ceramic, and the size of the extrusion die is: Outside circle Extrusion temperature 800°C ± 10°C.
[0059] (4) Pickling and hydraulic drawing: The obtained blank is pickled, the blank after extrusion is placed in a 15% sulfuric acid tank for pickling to remove surface oxides, and then subjected to hydraulic drawing; the hydraulic drawing is carried out on a hydraulic drawing machine with a specification of 0.6 MN. The specification of the alloy drawing die is: (Drawing process: ), uniform drawing.
[0060] (5) the rod after drawing deformation is straightened, polished and cut to size.
[0061] The copper alloy material is subjected to performance inspection, ten samples are taken from each batch, and the average value is taken. The metal material tensile test refers to the standard GB / T228, the metal material bending test is in accordance with the standard GB / T232, and the conductivity detection method is detected according to the provisions of the standard GB / T351 of the metal material resistance coefficient measurement method. The mechanical properties of the obtained copper alloy material are: tensile strength Rm=375MPa, cutting property=82%, elongation=14%, and conductivity=92%IACS.
[0062] The above examples are only part of the embodiments of the present application, and various improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications all fall within the protection scope of the present application.
Claims
1. A method for producing a high-conductivity free-cutting copper alloy material, characterized by comprising: The high-conductivity free-cutting copper alloy material comprises the following elements in percentage by weight: Te=0.6-0.7%, Fe=0.0020-0.0060%, B=0.0020-0.0060%, and Cu balance; and the preparation method comprises the following steps: (1) Melting: cathode copper is added into a melting furnace, scale graphite is used as a covering agent, and the temperature is raised to 1100-1200°C to completely melt the copper; boron-copper alloy, tellurium, and iron alloy elements are sequentially added into the copper liquid, the temperature is in the range of 1200°C±10°C, and the alloy elements are continuously stirred during the adding process to promote the uniform dispersion of the alloy elements in the copper liquid, the stirring speed is controlled to be 200-300 r / min, the stirring time is 10-15 min after each addition of the alloy elements, the furnace temperature is raised to 1200-1250°C after the addition is completed, and the alloy composition is homogenized for 15-20 min; (2) Casting: the alloyed copper liquid is cast into a high-purity graphite mold preheated to 200-300°C, and the casting temperature is 1170-1190°C; the casting speed is controlled to be 5-10 kg / min, the mold is kept stable during the casting process to avoid turbulence of the copper liquid, and a copper alloy ingot is obtained; (3) Extrusion: the copper alloy ingot obtained in step (2) is placed into an induction heating furnace, heated to 800°C±10°C, and kept for 30 min, and then water-sealed extrusion deformation processing is performed; (4) Pickling and hydraulic drawing: the extruded material obtained in step (3) is pickled to remove surface oxides, and then hydraulic drawing is performed, the total deformation amount is 50%, and the single-pass deformation amount is 15%-25%; (5) The rod after the drawing deformation is straightened, polished, and cut to size.
2. The method of producing a copper alloy material according to claim 1, characterized by, The cathode copper in step (1) contains Cu%≥99.95%; and the melting furnace is a medium-frequency induction melting furnace.
3. The method of producing a copper alloy material according to claim 1, characterized by, The scale graphite in step (1) contains C%≥99.95%.
4. The method of producing a copper alloy material according to claim 1, characterized by, The boron-copper alloy contains B%=5%±1%; the tellurium is high-purity tellurium, and contains Te%≥99.95%; and the iron is high-purity iron powder, and contains Fe%≥99.95%.
5. The method of producing a copper alloy material according to claim 1, characterized by, The water-sealed extrusion deformation processing in step (3) is performed on an 800 horizontal extruder, and the equipment specification is 8.0 MN.
6. The method of producing a copper alloy material according to claim 1, characterized by, The extrusion in step (3) adopts a reverse extrusion mode, and the extrusion temperature is 800°C±10°C.
7. The method of producing a copper alloy material according to claim 6, characterized by, The extrusion in step (3) adopts a metal-inlaid ceramic mold, and the extrusion ratio is 20-150.
8. The method of producing a copper alloy material according to claim 1, characterized by, The pickling in step (4) is performed by placing the extruded material in a sulfuric acid tank with a concentration of 15%-20%.
9. The method of producing a copper alloy material according to claim 1, characterized by, The drawing die in step (4) is an alloy drawing die or a diamond-coated drawing die, and the drawing die specification is: The hydraulic drawing is performed in a hydraulic drawing machine with a specification of 0.6 MN.
10. A copper alloy material prepared by the method of any one of claims 1-9.